Daily parenteral selenium therapy in critically ill patients: An updated systematic review and meta-analysis of randomized controlled trials. (February 2021) - Mousavi, Mir Ali; Saghaleini, Seied Hadi; Mahmoodpoor, Ata; Ghojazadeh, Morteza; Mousavi, Seyedeh Neda
Summary: Background and aim: Patients hospitalized at the intensive care unit (ICU) are more prone to oxidative stress. Antioxidants such as selenium (Se) may have beneficial effects on outcomes in these patients. Studies and systematic reviews in this field have inconclusive results. Methods: An updated systematic search was done to find clinical trials published in PubMed, Cochrane's library, ISI web of Science, Scopus, and Ovid databases from January 1980 up to April 2020, to assess the effects of daily Se supplementation on patient's survival, hospital and ICU stay, duration of mechanical ventilation, infection, acute renal failure (ARF) occurrence and serum creatinine levels. Results: From 1394 papers found in the first step of the search, after deleting duplicate findings, 24 studies were included in this meta-analysis. Results of the pooled random-effect size analysis of 24 trials showed no remarkable effect of daily parenteral Se administration on patient's hospital and ICU stay, duration of mechanical ventilation, infectious complications, ARF, survival and serum creatinine levels (p > 0.05). The subgroup analysis showed that daily parenteral Se administration (in doses higher than 1000 μg/d) increased the length of ICU stay by 4.48-folds (95%CI: −0.5, 9.46, p = 0.07). Parenteral Se supplementation at the first and following dose of ≤1000 μg reduced the number of ARF at the hospitalized patients by 76% and 45%, respectively (p = 0.02, and p = 0.05). Conclusions: High doses of Se increases days of ICU stay, but low doses decreases the number of ARF occurrence in ICU patients. More trials are needed to assess its effect on ARF occurrence.